Pagtubos [videorecording] isang kuwento ng kuwaresma - Cabreg, Yvonne Laforteza; De Leon, Noel.; Laforteza-Cabreg, Yvonne ([Cavite] Diocese of Imus)
An examination of Filipino practices during Lent and their relevance to Christ's passion and death.
Tagapagsalaysay, Er Ramos
Keywords: Lent -- Philippines; Religion